Competing Administrations in Palestine: Imperial Power and Settler Regimes in the British Empire. Issue 2 (November 2020) - Hogan, Adam
Abstract : This paper investigates the similarities between the British experiences with settlers in other instances of colonisation, and mandatory Palestine. It addresses the extent to which British officials were aware of, and understood the aims, intentions, and methods of the Zionist movement, as well as the consequences for the indigenous population. Utilising primarily British documents from the mandatory period, and the literature on settler-colonialism, this paper will address a gap in research on the imperial responsibility, and role in, the mandate's development. This examines the knowledge and intent of the British in the settler-colonial context, and British imperial history.